Top oil heat distribution pattern of ONAN corn oil based transformer with presence of hot spot study using FEMM - M. A. Husin; Nordiana Azlin binti Othman; N. A. Muhammad; H. Kamarden; M. S. Kamarudin (Institute of Advanced Engineering and Science, 2019)
Transformer thermal modelling is a crucial aspect to be considered as this may help the determination of heat capacity of transformer. This paper present, simulation study on Oil Natural Air Natural (ONAN) transformer heat distribution pattern with and without presence of hot spot temperature (HST). This paper aims to compare the effects of different HST value at different locations inside the transformer unit as well as to evaluate the top oil thermal behaviour of corn oil as cooling mechanism in a transformer. To achieve aforementioned objectives, three HSTs were introduced to the 30 MVA transformer winding to find the total heat build-up in the top of the transformer tank. The outcome of thermal properties is examined using x-y temperature plot. From the results found that the location of HST affects overall transformer’s temperature. HST at the top of the winding give a significant effect compared to when HST is at the bottom of the winding. It is also evident that the usage of corn oil reduced the temperature distribution of the transformer. The findings suggest that the temperature distribution study especially on transformer is important to monitor in-service transformer in a non-invasive manner.